Relationship of Limited Joint Mobility and Foot Deformities with Neurological Examination in Patients with Diabetes - Sanz-Corbalán, I.; Lázaro-Martínez, J. L.; García-Morales, E.; Aragón-Sánchez, J.; Carabantes-Alarcón, D.; García-Álvarez, Y. (Experimental and Clinical Endocrinology & Diabetes, 2013)
The aim is to define the association of forefoot deformity and limited joint mobility in the ankle and hallux joints in patients with diabetes mellitus subject to different diagnostic tests for diabetic neuropathy.Prospective study with 118 type 2 diabetic patients (68 men, mean age of 65.6±9.9 years) enrolled consecutively from the Diabetic Foot Unit of the Complutense University of Madrid subject to evaluation of plantar surface sensitivity by 10-g Semmes-Weinstein Monofilament, vibratory threshold by biothesiometer, and sudomotor dysfunction by Neuropad®. The patients presented with limited joint mobility of the ankle and the first metatarsophalangeal joints, and forefoot deformities were registered. Statistical analysis was done through a univariate model to test the association between neurological and biomechanical alteration.There was an association of abnormal Monofilament (p=0.01; OR=3.9) and biothesiometer tests (p=0.01; OR=2.6) with the presence of forefoot deformity. Furthermore, a relation was found between abnormal Monofilament (p=0.02; OR=4.8) and biothesiometer (p<0.00; OR=12.8) tests with limited mobility of the first metatarsophalangeal joint both in loading and off-loading. Abnormal sudomotor function test was related with limited joint mobility of the ankle joint with the knee flexed (p=0.04; OR=2.8).The results of this study show discordance between biomechanical abnormalities and neuropathy depending on the diagnostic test used. Tests that assess large myelinated nerve fibers are associated with the presence of deformities. Abnormal sudomotor function test is associated with limited joint mobility and this test has a greater capacity for selecting patients at risk.
Keywords: Diabetic Foot; Diabetic Neuropathy; Biomechanical Alterations; Limited Joint Mobility